Similarities and Differences in Theory of Mind Responses of Patients With Anorexia Nervosa With and Without Autistic Features - Sedgewick, Felicity; Leppanen, Jenni; Goh, Faith; Hayward, Hannah; Happé, Francesca; Tchanturia, Kate (Frontiers in Psychiatry, 2019)
Theory of Mind (ToM) is the ability to understand and represent mental states of others, a skill which plays a key role in how we interact with people around us. Difficulties with ToM have been posited as an underlying mechanism for autism and implicated in difficulties faced by those with anorexia nervosa (AN). This study examined, both quantitatively and qualitatively, the responses of women between the ages of 14 and 25 years on the Frith-Happé Triangle Animations, a well-validated test of ToM. Participants were split into healthy controls (HC), AN patients (AN), and AN patients with high levels of autistic features (AN+ASF). We found no significant quantitative differences between groups in performance on the task. Qualitatively there were differences between groups, such that AN patients, especially those in the AN+ASF group, were more focused on describing the videos than creating narratives, were more negative in their interpretations, and were much more anxious about their performance. These qualitative differences have clinical implications, including that not all AN patients with autistic features should be assumed to have difficulties with ToM, and that difficulties with ToM may be more a feature of traditional male presentations of autism.